Tax literacy among salaried individuals : Sabah and Sarawak's perspective / Amrizah Kamaluddin … [et al.] - Kamaluddin, Amrizah; Madi, Nero (2004)
The main objective of this study is to gauge the general level of tax literacy among salaried taxpayers in Sabah and Sarawak. This study is undertaken to shed light on our preparedness to face the challenge posed by the implementation of Self Assessment System (SAS) on salaried taxpayers beginning from the year 2004 where taxpayers are expected to be functionally literate to compute their own tax liabilities accurately. For the purpose of this study, samples were randomly taken from salaried taxpayers working in Kuching, Sibu, Bintulu, Miri, Sandakan, Tawau and Kota kinabalu.